Improved manufacture of hybrid membranes with bionanopore adapters capable of self-luting. Issue 1 (9th November 2018) - Altintoprak, Klara; Farajollahi, Farid; Seidenstücker, Axel; Ullrich, Timo; Wenz, Nana L; Krolla, Peter; Plettl, Alfred; Ziemann, Paul; Marti, Othmar; Walther, Paul; Exner, Daniela; Schwaiger, Ruth; et al.
Abstract : The authors' recent concept of bioinorganic filtration devices made up of solid-state membranes (SSMs) accommodating ring-shaped, ribonucleic acid (RNA)-stabilized tobacco mosaic virus (TMV) coat protein (CP) assemblies with central 4 nm holes as genetically encoded 'pore-in-pore' fittings, to convey size and charge specificity to the membranes' permeability, has been elaborated. Key developments for simplifying and finishing the unique combination apply to both soft- and hard-matter components: previous SSMs with millions of conical pores demanded sophisticated lithography to achieve a taper trapping the bionanopores upon insertion in a flow. Now focused helium (He) ion beam technology has enabled efficient, fast preparation of silicon nitride templates adapted to the nanorings. Proof-of-concept experiments reveal that negative charges imparted by nucleic acids exposed on the bionanopores might improve electrophoretic implantation further. Suitable peptides installed on the outer nanoring rim had been shown to nucleate spatially confined silica deposition from liquid precursors, which have been optimized in order to seal the annular gaps between bio and inorganic SSM pores by 'bionic glue'. Finally, two engineered CP variants and a modified scaffold RNA were established for novel TMV nanoring types with altered pore charges, which also allow installing accessory molecules for advanced filtration and conversion tasks.